Large-Scale Production of Anti-RNase A VHH Expressed in pyrG Auxotrophic Aspergillus oryzae - Elif Karaman; Alp Ertunga Eyüpoğlu; Lena Mahmoudi Azar; Serdar Uysal (Current Issues in Molecular Biology, 2023)
Nanobodies, also referred to as VHH antibodies, are the smallest fragments of naturally produced camelid antibodies and are ideal affinity reagents due to their remarkable properties. They are considered an alternative to monoclonal antibodies (mAbs) with potential utility in imaging, diagnostic, and other biotechnological applications given the difficulties associated with mAb expression. Aspergillus oryzae (A. oryzae) is a potential system for the large-scale expression and production of functional VHH antibodies that can be used to meet the demand for affinity reagents. In this study, anti-RNase A VHH was expressed under the control of the glucoamylase promoter in pyrG auxotrophic A. oryzae grown in a fermenter. The feature of pyrG auxotrophy, selected for the construction of a stable and efficient platform, was established using homologous recombination. Pull-down assay, size exclusion chromatography, and surface plasmon resonance were used to confirm the binding specificity of anti-RNase A VHH to RNase A. The affinity of anti-RNase A VHH was nearly 18.3-fold higher (1.9 nM) when expressed in pyrG auxotrophic A. oryzae rather than in Escherichia coli. This demonstrates that pyrG auxotrophic A. oryzae is a practical, industrially scalable, and promising biotechnological platform for the large-scale production of functional VHH antibodies with high binding activity.